2018
DOI: 10.3389/fpsyt.2018.00339
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Dynamic Functional Network Connectivity and Graph Properties in Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is a complex mood disorder characterized by persistent and overwhelming depression. Previous studies have identified abnormalities in large scale functional brain networks in MDD, yet most of them were based on static functional connectivity. In contrast, here we explored disrupted topological organization of dynamic functional network connectivity (dFNC) in MDD based on graph theory. One hundred and eighty-two MDD patients and 218 healthy controls were included in this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 67 publications
11
100
1
Order By: Relevance
“…They observed that MDD patients spent much more time in a weekly-connected State 2, which involved DMN regions and exhibited significantly decreased harmonic centrality involving the parietal lobule, lingual gyrus, and thalamus. The reduced dFC in DMN reported by the two studies (Kaiser et al, 2016;Zhi et al, 2018) is in agreement with our findings that MDD is characterized by lower EC in DMN. In another graph theory study, Zheng et al (2015) reported that the connectivity degree was increased for the right anterior insula and decreased between the DMN and EXE in MDD, which supported the triple network model (Menon, 2011).…”
Section: Relevance To Other Network Measuressupporting
confidence: 93%
See 2 more Smart Citations
“…They observed that MDD patients spent much more time in a weekly-connected State 2, which involved DMN regions and exhibited significantly decreased harmonic centrality involving the parietal lobule, lingual gyrus, and thalamus. The reduced dFC in DMN reported by the two studies (Kaiser et al, 2016;Zhi et al, 2018) is in agreement with our findings that MDD is characterized by lower EC in DMN. In another graph theory study, Zheng et al (2015) reported that the connectivity degree was increased for the right anterior insula and decreased between the DMN and EXE in MDD, which supported the triple network model (Menon, 2011).…”
Section: Relevance To Other Network Measuressupporting
confidence: 93%
“…Zhi et al (2018) applied graph theory to examine the impaired topological organization of dFC in MDD and identified five dynamic functional states, three of which showed significant group differences. Zhi et al (2018) applied graph theory to examine the impaired topological organization of dFC in MDD and identified five dynamic functional states, three of which showed significant group differences.…”
Section: Relevance To Other Network Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In another clinical condition, a study found that individuals with major depressive disorder (MDD) more time in a state with weak functional connectivity strength across the brain (weakly-connected dFC state) associated with self-focused thinking (Zhi et al, 2018). Atypical dFC patterns were significantly correlated with both depressive symptoms and cognitive performance (Zhi et al, 2018).…”
Section: Dynamic Functional Connectivity (Time-varying Functional Patmentioning
confidence: 99%
“…In particular, Kaiser et al (2016) found that meditation in depressed patients is associated with abnormal communication patterns of brain fluctuations (Kaiser et al, 2016). Zhi et al (2018) used the sliding-window algorithm to identify three types of node damage which were related to the severity of depressive symptoms and cognitive ability. Wang et al (2019) found decreased DFC variability between the anterior DMN and the right CEN compared with controls (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%